Growing Up in Australia: The Longitudinal Study of Australian Children: 2009-2010 Annual Report - (:unkn) unknown (My University, 2011)
The Longitudinal Study of Australian Children (LSAC) commenced in 2004. It collects a range of information about the physical health and social, cognitive and emotional development of Australian children from infancy and early childhood, following two cohorts of different age groups. The annual report for the 2009/2010 period provides an overview of the study and recent key findings, with the children now aged 4-5 years and 8-9 years. Significant events for the year include the release of Wave 3 data in August 2009, the commencement of Wave 4 data collection in March 2010, and the hosting of the 2nd LSAC Research Conference in Melbourne in December. The report also lists key personnel, publications, and presentations.
2009-2010
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Surveys and Survey Methodology